Effect of emodin on growth performance, antioxidant status, intestinal morphology and heat shock protein gene expressions of freshwater prawn (Macrobrachium rosenbergii) - Dawit Adisu Tadese; Gashaw Tesfaye; Metekia Tamiru; Lishan Alemu; Fikremariam Geda (Journal of Fisheries, 2022)
The purpose of this study was to assess the effect of emodin on biochemical variables, antioxidant activity, heat shock protein gene expression and prawn intestinal morphology (Macrobrachium rosenbergii). Three feeds containing 0 mg kg–1 (T1, control group), 25 mg kg–1 (T2) and 50 mg kg–1 (T3) of emodin were formulated and fed for eight weeks. Alanine aminotransferase, total cholesterol and triglyceride contents were significantly lowered although glucose tended to increase following the emodin remedy. Superoxide dismutase variables in haemolymph were dramatically upgraded, whilst malondialdehyde and superoxide anion situations were significantly lowered when compared to control. Emodin supplementation had no influence on glutathione peroxidase contents. Emodin remedy dropped the expression of HSP60 and HSP90 genes in comparison to the control. In T2, the intestinal epithelial cells were complete, well-organised and tightly affixed to the basement membrane, in discrepancy to the slightly disunited basement membrane in the control group. The emodin-treated prawn individuals had a thicker and full intestinal morphology than the control groups. Supplementation with emodin at dosages of 25 mg kg–1 improved growth performance, blood biochemical, antioxidant capacity and immune gene expression.